The return of the native : Indians and myth-making in Spanish America, 1810-1930 - Earle, Rebecca (e-Duke books scholarly collection., 2007)
The Return of the Native offers a look at the role of preconquest peoples such as the Aztecs and the Incas in the imagination of Spanish American elites in the first century after independence.